Efficacy of oxidized regenerated cellulose combined with fibrin glue in reducing pulmonary air leakage after segmentectomy in a porcine lung model - Yang, He; Dong, Zhiqiang; Wang, Hongya; Liu, Zicheng; Sun, Wenbo; Wang, Kun; Xu, Xinfeng; Wen, Wei; Wang, Jun; Chen, Liang; Zhu, Quan (Frontiers in Bioengineering and Biotechnology, 2022)
Objectives: Pulmonary air leakage is a common complication following lung resection. We have designed a new method combining oxidized regenerated cellulose and fibrin glue to cover the intersegmental plane in clinical lung segmentectomy to prevent postoperative air leakage. In this study, an excised porcine lung segmentectomy model was created to validate its adhesive strength and effect on reducing air leakage. Methods: In the pre-experiment, six different larger lung segments were separated using electrocautery on the fresh isolated porcine lungs. The air leakage degree and operation time of the lung segments were comprehensively evaluated to select the most suitable target segment for establishing the segmentectomy models. According to the different materials covered on the intersegmental plane, these models were randomly divided into four groups: group A used fibrin glue and oxidized regenerated cellulose mesh; group B used fibrin glue and polyglycolic acid sheet; group C used fibrin glue; group D was the blank control group. The MALP of the selected target segment in each group was measured , and histological assessment was performed on the sealed area samples from the four groups. Results: The operation time of the a segment of the right cranial lobe (R1a) was shorter than the other segments (p < 0.05), and there was no significant difference in the air leakage pressures between the six isolated segments (p = 0.76); thus, R1a was chosen for segmentectomy. The MALP was significantly higher in group A (41.8 ±4.5 cmH2O) than in groups C (28.1 ± 2.3 cmH2O) and D (17.3 ± 1.2 cmH2O) (both p < 0.001). The MALP of group B was significantly higher than that of group A (p < 0.001), whereas that of group C was significantly higher than that of group D (p < 0.001). Histological examination confirmed that the combined use of fibrin glue and ORC or PGA patch adhered more firmly to the intersegmental plane than that of fibrin glue alone. Conclusions: ORC may be an effective alternative material to replace PGA sheet to combine with fibrin glue for preventing air leakage after segmentectomy.